2020
DOI: 10.1021/acs.iecr.0c03850
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oxidative Dehydrogenation of n-Butane to C4-Olefins over a VOx/CeO2–γAl2O3 Catalyst in Gas-Phase Oxygen-Free Conditions

Abstract: In the present research, the phenomenologically based kinetics of the oxidative dehydrogenation (ODH) of n-butane to C4-olefins over a newly developed VO x /CeO2–γAl2O3 catalyst was investigated. The catalyst was formulated by impregnating 5 wt % V in a 0.2 wt % Ce-modified CeO2–γAl2O3 support. NH3-temperature-programmed desorption indicated the presence of both low- and high-temperature acid sites on the catalyst surface. Temperature-programmed reduction TPR/temperature-programmed oxidation (TPO) analyses sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…The opposing view is that surface lattice oxygen and sub‐surface lattice oxygen play critical roles in the formation of the desired and undesired products. Previous studies by present research group showed that the latter case usually involves the anaerobic conversion of paraffins to light olefins [40] . In this study, the oxygen involved in the oxidative conversion of n‐hexane mainly results from the VO x component of the catalyst.…”
Section: Kinetic Modellingmentioning
confidence: 67%
See 3 more Smart Citations
“…The opposing view is that surface lattice oxygen and sub‐surface lattice oxygen play critical roles in the formation of the desired and undesired products. Previous studies by present research group showed that the latter case usually involves the anaerobic conversion of paraffins to light olefins [40] . In this study, the oxygen involved in the oxidative conversion of n‐hexane mainly results from the VO x component of the catalyst.…”
Section: Kinetic Modellingmentioning
confidence: 67%
“…The hydrogen temperature program reduction (H 2 ‐TPR) analysis was conducted to study the reducibility of the catalyst samples. This analysis specified the catalysts’ active temperature range as well as the available lattice oxygen for the oxidative conversion of n‐hexane [40] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations